(untitled) (Atlas Journal of Biology, 2017)
The croaking gourami (Trichopsis vittatus) exhibits two phenotypes associated with humeral spotting. Fish possess a prominent, dark humeral patch or spot located behind the operculum or lack this spotting pattern. Segregation patterns observed from the progenies of eleven different crosses support the hypothesis that the inheritance of humeral spotting in T. vittatus is controlled by the action of a single autosomal locus, with complete dominance of the allele controlling the spotted phenotype.